Is There Anti-Fittingness? - Selim Berker (Ergo, An Open Access Journal of Philosophy)
The permissible and the forbidden are privative opposites: each is a lack of the other. The good and the bad are, by contrast, polar opposites: badness is anti-goodness, not non-goodness. What about the fitting and the unfitting, the appropriate and the inappropriate, the apt and the inapt, the warranted and the unwarranted? Is unfittingness non-fittingness or anti-fittingness, inappropriateness non-appropriateness or anti-appropriateness? This essay argues that each of these “aptic” categories stands in a privative rather than a polar relation to its opposite. More generally, there is no coherent notion of anti-fittingness, no inversely charged flipside to aptness, to be found. In order to establish these claims, a taxonomy of different types of oppositeness is proposed, and several tests for distinguishing distinct varieties of opposites are developed. What emerges is a better appreciation of the structural characteristics of fittingness and the other aptic categories, as well as an argument for taking up the nature of oppositeness as a serious philosophical topic that is ripe for further exploration.